EVALUASI KESESUAIAN LAHAN KERING UNTUK TANAMAN PANGAN DI KECAMATAN KUBUTAMBAHAN KABUPATEN BULELENG - Made Sri Sumarniasih; Suarni Apriciila Benedigta Zebua; Made Antara (Universitas Lambung Mangkurat, 2022)
Dry land is land whose use for the development of agricultural commodities is limited, due to constraints on the availability of nutrients and water. The research objectives are: to identify the suitability of dry land for upland rice, corn and peanuts; identify limiting factors and improvement efforts to increase land productivity. The method used is a survey to determine the characteristics of the land in the field and to take soil samples that are analyzed in the laboratory. Determination of sample points based on the results of overlapping maps of soil types, land use maps, slope maps using QGIS 3.4, so that a homogeneous land unit map (SLH) is obtained, and 6 SLH is obtained as observation points. The results of field and laboratory data analysis were matched with the growing requirements for upland rice, corn and peanuts. The actual land suitability for upland rice, corn, and peanuts is classified as S2 (fairly suitable) to N (not suitable). The limiting factors are slope, erosion hazard, temperature, texture, rainfall, pH, N-total, P2O5, Cation Exchange Capacity, Base Saturation, availability of oxygen, and C-organic. Improvement efforts that must be done are making terraces, fertilizing urea, fertilizers containing phosphate, mulching using plant residues, giving organic matter, and improving drainage. After improving the limiting factors that can be improved, the potential land suitability classes for upland rice, corn and peanuts are S1 (very suitable), S2 (fairly suitable) and S3 (marginally appropriate).